The relationship between social hypocrisy in organizational justice among governmental primary school teachers in Al Quwaysimeh District - Ayah Alabsi (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims to identify the relationship between social hypocrisy in organizational justice among governmental primary school teachers in Al Quwaysimeh District. The study was applied to a random sample consisting of (288) teachers. To collect the study data, the researcher constructed a questionnaire for social hypocrisy, and developed another questionnaire for organizational justice. The reliability and validity of both tools were affirmed. Among the most prominent results of the study was that the degree of practice of the primary school teachers in Al Qweismeh district for the behavior of social hypocrisy and organizational justice in their schools was moderate. There was a statistically significant negative correlation between the degree of practice for the behavior of social hypocrisy and the prevailing organizational justice in their schools. The Results also exhibited that there was statistically significant differences in the degree of practice teachers' for the behavior of social hypocrisy attributed to the gender variable in favor of males, while there was no statistically significant differences attributable to experience variable. Based on these results, the researcher recommended that teachers' professional development activities, include special quality programs to help teachers acquire positive attitudes and values based on honesty, equality and justice within and outside educational institutions.